A Direct Measurement of Vibration on the HDPE Structure of POLBENG Research Boat - Muhammad Alimul Hafiz; Muhammad Sidik Purwoko; Fazrian; Rizky Chandra Ariesta; Jamal; Arief Teguh Pribadi; Diki Arnanda; Mhd Vikri Ardiyanto; M Ibrahim Anselistyo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The adoption of High Density Polyethylene (HDPE) as the primary material for boat structures has increased significantly in recent years. In response to contemporary challenges and to facilitate research requirements, Polytechnic of Bengkalis (POLBENG) constructed a research boat utilizing HDPE. Nevertheless, further research on the response of the HDPE structure to vibrations generated by the main propulsion engine remains insufficiently intensive. Therefore, a direct measurement of ship vibration is conducted utilizing vibration sensors, namely Witmotion WTVB02-485. Both inside and outside of the accommodation rooms, measurements were taken. By comparing the vibrational velocity's Root Mean Square (RMS) to standards established by the American Bureau of Shipping (ABS), a classification society, structural assessment was evaluated. Furthermore, resonance events were discovered by comparing the Blade Passing Frequency (BPF) with the recorded peak frequency output. The HDPE structure seems to be dependable, according to the measurement findings at both locations. The RMS of 0.020 mm/s and a peak frequency of 33.31 Hz were recorded inside the accommodation area, whereas 0.013 mm/s and 31.52 Hz were recorded outside.